Polycystic ovary syndrome and offspring risk of congenital heart defects: a nationwide cohort study. Issue 10 (14th August 2020) - Schmidt, A B; Lund, M; Wohlfahrt, J; Melbye, M
Abstract: STUDY QUESTION: Is maternal polycystic ovary syndrome (PCOS) associated with increased offspring risk of congenital heart defects? SUMMARY ANSWER: This study does not support a strong association between PCOS and an increased risk of congenital heart defects. WHAT IS KNOWN ALREADY: In addition to affecting reproductive health, PCOS may involve insulin resistance. Maternal pregestational diabetes is associated with an increased risk of congenital heart defects and therefore PCOS may increase the risk of congenital heart defects in the offspring. STUDY DESIGN, SIZE, DURATION: In this nationwide cohort study, we used data from Danish health registers collected from 1995 to 2018. The study included 1 302 648 offspring and their mothers. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants were live singleton offspring born during the study period. Information on maternal PCOS and offspring congenital heart defects was obtained from the National Patient Register. Logistic regression analysis was used to compute prevalence (odds) ratio (PR) of the association between PCOS and offspring congenital heart defects. MAIN RESULTS AND THE ROLE OF CHANCE: Among 1 302 648 live-born singletons, 11 804 had a mother with PCOS. Of these, 143 offspring had a congenital heart defect (prevalence 121 per 10 000) as compared with 12 832 among mothers without PCOS (prevalence 99 per 10 000). The adjusted PR was 1.22, 95% CI 1.03–1.44 comparing prevalence of congenital heart defects in offspring of women with PCOS with offspring of women without. After adjusting for the potentially mediating effect of pregestational diabetes, the PR was 1.16, 95% CI 0.98–1.37. LIMITATIONS, REASONS FOR CAUTION: PCOS may be underdetected in the National Patient Register. However, we expect that the mothers that we identified with PCOS truly had PCOS, thus, the estimated associations are not likely to be affected by this misclassification. The study does not provide evidence to rule out a moderate or weak association. WIDER IMPLICATIONS OF THE FINDINGS: These findings provide reassurance to clinicians counselling pregnant women with PCOS that the disease does not pose a markedly increased risk of offspring congenital heart defects. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by the Novo Nordisk Foundation. M.L. reports personal fees from Dansk Lægemiddel Information A/S outside the submitted work. The remaining authors have no conflicts of interest TRIAL REGISTRATION NUMBER: N/A